Mental Effort When Playing, Listening, and Imagining Music in One Pianist’s Eyes and Brain - Endestad, Tor; Godøy, Rolf Inge; Sneve, Markus Handal; Hagen, Thomas; Bochynska, Agata; Laeng, Bruno (Frontiers in Human Neuroscience, 2020)
We investigated “musical effort” with an internationally renowned, classical, pianist while playing, listening, and imagining music. We used pupillometry as an objective measure of mental effort and fMRI as an exploratory method of effort with the same musical pieces. We also compared a group of non-professional pianists and non-musicians by the use of pupillometry and a small group of non-musicians with fMRI. This combined approach of psychophysiology and neuroimaging revealed the cognitive work during different musical activities. We found that pupil diameters were largest when “playing” (regardless of whether there was sound produced or not) compared to conditions with no movement (i.e., “listening” and “imagery”). We found positive correlations between pupil diameters of the professional pianist during different conditions with the same piano piece (i.e., normal playing, silenced playing, listen, imagining), which might indicate similar degrees of load on cognitive resources as well as an intimate link between the motor imagery of sound-producing body motions and gestures. We also confirmed that musical imagery had a strong commonality with music listening in both pianists and musically naïve individuals. Neuroimaging provided evidence for a relationship between noradrenergic (NE) activity and mental workload or attentional intensity within the domain of music cognition. We found effort related activity in the superior part of the locus coeruleus (LC) and, similarly to the pupil, the listening and imagery engaged less the LC–NE network than the motor condition. The pianists attended more intensively to the most difficult piece than the non-musicians since they showed larger pupils for the most difficult piece. Non-musicians were the most engaged by the music listening task, suggesting that the amount of attention allocated for the same task may follow a hierarchy of expertise demanding less attentional effort in expert or performers than in novices. In the professional pianist, we found only weak evidence for a commonality between subjective effort (as rated measure-by-measure) and the objective effort gauged with pupil diameter during listening. We suggest that psychophysiological methods like pupillometry can index mental effort in a manner that is not available to subjective awareness or introspection.